Corporate sustainability reporting in the European Union – Quo vadis, EU lawmaker? - Wojnowska-Radzińska, Julia (Ruch Prawniczy, Ekonomiczny i Socjologiczny, 2025)
The Corporate Sustainability Reporting Directive (CSRD) aims to ensure that companies transparently disclose their sustainability-related activities, providing stakeholders with reliable and comparable information. The CSRD stipulates that mandatory reporting must be conducted in accordance with the European Sustainability Reporting Standards (ESRS). However, from the outset, these reporting standards have raised numerous concerns regarding their complexity and level of detail, which has initiated an active debate within the European Union. As a result, the European Commission has proposed a set of simplifications to these regulations. The purpose of this article is both to review the CSRD and to examine the potential implications of the changes proposed by the European Commission in the simplification package known as ‘Omnibus I.’ The primary research method employed is the dogmatic-legal method, supplemented by the theoretical-legal method.